2021
DOI: 10.1016/j.ajpc.2021.100255
|View full text |Cite
|
Sign up to set email alerts
|

Population awareness of cardiovascular disease risk factors and health care seeking behavior in the UAE

Abstract: Objectives We aimed to determine the awareness, knowledge, and attitude of people residing in Dubai, United Arab Emirates, regarding cardiovascular disease (CVD) risk factors. Our aim was to further identify prospects to increase awareness of modifiable CVD risk factors and influence behavior. Methods This observational study was conducted in Dubai: a global city in the United Arab Emirates. Participants were selected using simple randomization approach in primary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…This finding aligns with previous studies that have also demonstrated a correlation between higher education levels and better understanding of CVDs (21,31,43). It stands to reason that individuals with greater educational attainment are exposed to more information about diseases, thereby fostering higher CVDs knowledge scores (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding aligns with previous studies that have also demonstrated a correlation between higher education levels and better understanding of CVDs (21,31,43). It stands to reason that individuals with greater educational attainment are exposed to more information about diseases, thereby fostering higher CVDs knowledge scores (18).…”
Section: Discussionsupporting
confidence: 91%
“…Investigating the attitudes of older individuals toward CVDs can provide valuable insights into their perceptions, beliefs, and potential barriers to effective prevention and management (17). To promote these positive attitudes, public health campaigns should underscore the benefits of prevention, raise awareness about the importance of regular check-ups, and offer education on the long-term advantages of treatment adherence (18).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the combination of the enabling factors of high prevalence, low awareness, and poor hypertension control calls for an urgent response in line with Sustainable Development Goals (SDG) target 3.4 on Non-communicable Diseases (NCDs) to lower hypertension prevalence or control BP through both improved prevention and improving early-stage treatment cascades [ 2 , 31 ]. The changing prevalence of hypertension in the UAE is mainly due to changing lifestyles with lower physical activity and a shift from a traditional diet that is high in fiber to energy-dense processed food high in fat, sugar, and salt [ 32 , 33 , 34 ]. Furthermore, studies consistently reported a significantly increased burden of overweight and obesity [ 35 ], metabolic syndrome [ 36 ], and cardiovascular risk factors [ 37 ] among the younger population in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study’s cross-sectional design limits our ability to establish causation and temporal changes in knowledge and awareness levels cannot be fully captured. The sample primarily represents specific regions in Saudi Arabia, potentially limiting the generalizability of findings to the entire population [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%